Eye movement and postural sway in dyslexic children during sitting and standing - Razuk, Milena; Barela, Jose Angelo [UNESP]; Peyre, Hugo; Gerard, Christophe Loic; Bucci, Maria Pia [UNESP] (Elsevier B.V., 2018)
In this study, we investigated the eye movement and postural control performance in dyslexic children while reading text and performing Landolt reading when sitting and standing. Fifteen dyslexic and 15 non-dyslexic children were asked to sit in a chair while the eye movements were recorded, and were then asked to stand on an unstable platform while eye movements and postural sway were recorded simultaneously at the time of Landolt reading and text reading. Eye movements were recorded binocularly by Mobile EyeBrain Tracker (MobileT2 (R), SuriCog) and center of pressure excursions were recorded by Multitest Equilibre (by Framiral (R)). The dependent variables for visual performance in the reading tasks were: total reading time, mean duration of fixation, number of pro- and retro-saccades, and amplitude of pro-saccades. The dependent variable for postural performance was the center of pressure area. The results showed that dyslexic children spent more time reading the text compared to non-dyslexic children (p < 0.02). However, no difference was observed for the Landolt reading task (p > 0.05). Dyslexic children performed longer fixations in the sitting condition as compared to the standing (p < 0.03), namely, higher number of pro- (p < 0.001) and retro- saccades (p < 0.001), and smaller pro-saccades amplitude (p < 0.001). Therefore, when the linguistic and semantic requirements are not involved in the reading task, dyslexic children perform similar to non-dyslexic children even in different task requirements (p > 0.05). Finally, postural performance was poorer in dyslexic children than in non-dyslexic children in both the reading tasks (p < 0.02). However, postural control performance, which was poor in dyslexic children, is not related to lexical and semantic reading requirements.
Keywords: Posture; Eye movement; Reading; Dyslexia